Hubungan antara usia, paritas dan riwayat kuretase dengan kejadian plasenta previa di Rumah Sakit Muhamamdiyah Palembang Tahun 2023 - Nirmalasari, Nirmalasari; Chairuna, Chairuna; riski, merisa (NHM PRESS, 2023)
Placenta previa is a condition in which the placenta implants the lower uterine segment so that it covers all or part of the os in the uterus or birth canal and makes it difficult for the baby to be born. In developed countries, the prevalence of placenta previa ranges from 0.26% to 2.00% of all pregnancies. While some experts claim that between 2.4 and 3.56% of all births in Indonesia experience placenta previa. The purpose of this study was to determine the relationship between age, parity and history of curettage simultaneously with the incidence of placenta previa at Palembang Muhammadiyah Hospital in 2023 . Type and Design Research is quantitative using an analytic survey method with an approachcross sectional. The population in this study were all pregnant women who were treated at the Muhammadyah Palembang Hospital in 2022, totaling 1,716. The sample used amounted to 95 respondents. The results of the univariate analysis obtained from 95 respondents, there were 10 respondents (10.5%) who had placenta previa and 85 respondents (89.5%) who did not. The results of the chi-square statistical test for the variable maternal age obtained ρ value = 0.000, parity variable ρ value = 0.012 and curettage history variable ρ value = 0.000 less than α = 0.05 indicating that there is a significant relationship between maternal age, parity and history of curettage with the incidence of placenta previa at the Palembang Muhammadiyah Hospital in 2023. Suggestions for the leadership of the Palembang Muhammadyah Hospital are that it is hoped that the results of this research can be used as a basis or reference for the hospital in making health programs for pregnant women, especially the problem of placenta previa.